Sharia Economic Da'wah Concepts and Strategies Based on Surah As-Shaff (Verses 1-4) - Wahyuddin, Wahyuddin; Syam, Ilma Radia; Basri, Halimah; Abubakar, Achmad (Jurnal Ilmu Manajemen Profitability, 2024)
Islamic economic da'wah is increasingly important in the current era of globalization, where fair, moral, and economic values in accordance with Islamic principles are increasingly sought after. Based on surah As-Saf verses 1-4 in the Qur'an, understanding the concepts and strategies of Islamic economic da'wah is very important. These verses emphasize the concept of tawhid, which is the recognition of the oneness of Allah and servitude to Him. This concept is the basis of Islamic economic practice, where every economic action begins and ends with the realization that we obey Allah swt. These verses also remind how important the relationship between words and actions is, suggesting that the values and principles of Islamic economics should be applied in everyday life. This research is a descriptive qualitative research using library research method. The results of this study indicate that the concept and strategy of Islamic economic da'wah based on surah As Shaf verses 1-4 include understanding that everything in the universe belongs to Allah, consistency between words and actions, integrity and morality in business, as well as cooperation and coordination in achieving the same goal.